Transformasi Geometri dalam Arsitektur Islam: Eksplorasi Etnomatematika di Museum Islam Indonesia Hasyim Asy’ari - Mustofiyah, Heni; Melia Sari, Yurizka (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2025)
This study aims to explore the concept of geometric transformation in the ornamentation and architecture of the Hasyim Asy'ari Islamic Museum as part of ethnomathematics studies. The method used is descriptive qualitative with an ethnographic approach. Data were collected through direct observation, interviews with museum staff, and visual documentation. The results showed that some building elements and museum ornaments reflect geometric transformations such as translation, reflection, rotation and dilation. For example, the roof of the museum represents reflection on the y-axis, while the khat kufi ornaments show translation, reflection, and 90-degree rotation. These findings make an important contribution to the development of local culture-based math learning media. This research also shows that ethnomathematics can be an effective approach to contextualize mathematical materials in real life, especially in the form of historical buildings with cultural and religious values.